2018
DOI: 10.1111/ppl.12832
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of flowering by green light depends on its photon flux density and involves cryptochromes

Abstract: Photoperiodic lighting can promote flowering of long-day plants (LDPs) and inhibit flowering of short-day plants (SDPs). Red (R) and far-red (FR) light regulate flowering through phytochromes, whereas blue light does so primarily through cryptochromes. In contrast, the role of green light in photoperiodic regulation of flowering has been inconsistent in previous studies. We grew four LDP species (two petunia cultivars, ageratum, snapdragon and Arabidopsis) and two SDP species (three chrysanthemum cultivars and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
(60 reference statements)
0
7
0
1
Order By: Relevance
“…2017 ). These studies have shown that in the process of floral induction, plants need to first sense various environmental signals, such as light ( Meng and Runkle 2019 ) and temperature ( Verhage et al. 2014 ), combine them with the internal state ( Simpson 2004 ) and finally summarize the signal via floral integrators, such as FLOWERING LOCUS T ( FT ) ( Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…2017 ). These studies have shown that in the process of floral induction, plants need to first sense various environmental signals, such as light ( Meng and Runkle 2019 ) and temperature ( Verhage et al. 2014 ), combine them with the internal state ( Simpson 2004 ) and finally summarize the signal via floral integrators, such as FLOWERING LOCUS T ( FT ) ( Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to physiological and morphological changes, light from different regions of the electromagnetic spectrum is also responsible for mediating genetic responses, which trigger the biosynthesis of chlorophylls, carotenoids, phenolic acids, flavonoids, anthocyanidins, anthocyanins, and glucosinolates (Figure 3). Specific photoreceptors (Figures 1 and 3), such as UV RESISTANCE LOCUS 8 (UVR8) as the main UV photoreceptor [44]; cryptochromes, phototropins, and zeitlupe family proteins as the UV-A/blue/green photoreceptors [45,46]; and phytochromes as red and far-red photoreceptors [47], are in charge of absorbing light signals that the plant receives. When UV/blue light activates photoreceptors, they activate transcription factors, which link with elongated hypocotyl-5 (HY5) as the main phytoene synthase (PSY) stimulator [48].…”
Section: Light Stresses As Elicitors Of the Biosynthesis Of Phytochem...mentioning
confidence: 99%
“…Although no photoreceptors are known yet to be able to sense green light, supplementation of green light in some plant species promotes growth. Green light also controls the flowering in ornamental plants like petunia, ageratum, chrysanthemum, and marigold [ 281 ]. Flowering in Arabidopsis under green light is mediated by CRY2 [ 281 ].…”
Section: Approaches Involving Photoreceptors For Climate-smart Crop P...mentioning
confidence: 99%
“…Green light also controls the flowering in ornamental plants like petunia, ageratum, chrysanthemum, and marigold [ 281 ]. Flowering in Arabidopsis under green light is mediated by CRY2 [ 281 ]. Short pulses of UV light not only increased the yield and content of bioactive compounds but also reduced the infection during the storage of potato, tomato, and almonds.…”
Section: Approaches Involving Photoreceptors For Climate-smart Crop P...mentioning
confidence: 99%